2015
DOI: 10.1007/s00442-015-3514-0
|View full text |Cite
|
Sign up to set email alerts
|

Population differentiation in a Mediterranean relict shrub: the potential role of local adaptation for coping with climate change

Abstract: Plants can respond to climate change by either migrating, adapting to the new conditions or going extinct. Relict plant species of limited distribution can be especially vulnerable as they are usually composed of small and isolated populations, which may reduce their ability to cope with rapidly changing environmental conditions. The aim of this study was to assess the vulnerability of Cneorum tricoccon L. (Cneoraceae), a Mediterranean relict shrub of limited distribution, to a future drier climate. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Our assessment of changes in the expression of genetic variation along stress gradients shows that population differentiation may indeed be affected by stress levels (55% of the reviewed studies showed greater or lower differentiation in stressful environments; see e.g. Hansen, Garcia, & Ehlers, ; Lázaro‐Nogal et al, ), which suggests that this aspect needs to be considered during experimental design.…”
Section: Discussionmentioning
confidence: 93%
“…Our assessment of changes in the expression of genetic variation along stress gradients shows that population differentiation may indeed be affected by stress levels (55% of the reviewed studies showed greater or lower differentiation in stressful environments; see e.g. Hansen, Garcia, & Ehlers, ; Lázaro‐Nogal et al, ), which suggests that this aspect needs to be considered during experimental design.…”
Section: Discussionmentioning
confidence: 93%
“…However, these populations are located at the dry edge of the species’ distribution range, and strong selection pressures related to water availability may be selecting drought‐adapted phenotypes, as has been suggested for marginal populations of other species (Kirkpatrick & Barton, 1997; Lesica & Allendorf, 1995), including Tertiary relicts such as Ramonda myconi (Muller et al., 1997). An experimental study with C. tricoccon adds support to this hypothesis, showing that dry‐edge populations (e.g., CA) may be locally adapted, as they exhibited multiple functional traits that favored drought tolerance (Lázaro‐Nogal et al., 2015). It is then likely that low genetic diversity and high divergence in these populations are explained by past strong directional selection combined with isolation‐driven low gene flow and strong genetic drift.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, we could expect that the trees in these drier ecosystems may be more adapted to water stress (Arndt et al 2015), and that the species growing in generally moister conditions could be most sensitive to extreme drought events (Jump et al 2017). Similarly, individuals growing nearer the dry range edge of their species may be more sensitive, but not necessarily, as local adaptation could play a role in counteracting the effects of drier conditions (L azaro-Nogal et al 2016). Current uncertainty about which areas are likely to be the most vulnerable to drought is an obstacle for conservation and management planning, while gaps in our understanding of the physiological explanations for drought-induced mortality, and high variation between locations and species make long-term and broad-scale predictions of forest vulnerability and community composition difficult (McDowell et al 2013;Meir et al 2015).…”
Section: Introductionmentioning
confidence: 99%